2012
DOI: 10.3945/jn.112.158147
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotics and the Health Benefits of Fiber: Current Regulatory Status, Future Research, and Goals,

Abstract: First defined in the mid-1990s, prebiotics, which alter the composition and activity of gastrointestinal (GI) microbiota to improve health and well-being, have generated scientific and consumer interest and regulatory debate. The Life Sciences Research Organization, Inc. (LSRO) held a workshop, Prebiotics and the Health Benefits of Fiber: Future Research and Goals, in February 2011 to assess the current state of the science and the international regulatory environment for prebiotics, identify research gaps, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(124 citation statements)
references
References 99 publications
2
113
0
9
Order By: Relevance
“…In fact, recent studies on humans and mice (Neyrinck et al, 2011 a and b;Brownawell et al, 2012) have suggested that chitin may be useful in restore compositional balance of the intestine microbial community and in improving colonic function even when a high fat diet is consumed.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent studies on humans and mice (Neyrinck et al, 2011 a and b;Brownawell et al, 2012) have suggested that chitin may be useful in restore compositional balance of the intestine microbial community and in improving colonic function even when a high fat diet is consumed.…”
Section: Discussionmentioning
confidence: 99%
“…Insight into the potential effects of prebiotic and/or probiotic intervention on the gut microbiota can be gained (6). It is well-recognized that prebiotics (e.g., resistant starch, nondigestible oligosaccharides, and sugar alcohols) resist hydrolysis by mammalian enzymes, but are fermented by intestinal bacteria to yield short chain fatty acids (SCFAs), mainly acetic, propionic and butyric acids, eventually stimulating the growth and/or activity of intestinal bacteria that are potentially associated with health (7).…”
mentioning
confidence: 99%
“…Existen diferentes estudios que indican un posible efecto beneficioso de los prebióticos sobre la disponibilidad de los minerales y de algunos oligoelementos incluidos en los alimentos, influyendo tanto en su absorción, su retención como en su uso por el organismo (12,13). De entre los prebióticos, los más estudiados son los derivados de la achicoria: la inulina y los fructooligosacáridos (FOS) (14), cuyo consumo está relacionado con un incremento en la absorción del calcio y magnesio a través del aumento de la solubilización de sus sales y de su absorción (15).…”
Section: Introductionunclassified